Pelatihan Penggunaan Media Pembelajaran Matematika Menggunakan Papan Pintar Perkalian Untuk Meningkatkan Kemampuan Aritmatika Siswa - Muhammad Farid Nasrulloh; Nailu Ainil Basyiroh; Nanang Khuzaini; Fitri Umardiyah; Khusnul Khotimah (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2024)
Education is a process of maturing the quality of life. Humans carry out education in order to improve and increase their standard of living. Basic mathematics is a branch of mathematics which is often referred to as arithmetic, which studies the arithmetic operations of addition, subtraction, multiplication and division. Based on the results of a survey by conducting interviews with several class II and III students, many class II and III students at SDN Betek I did not master basic multiplication calculations, had difficulty calculating quickly and lacked interest in counting because the learning media was too monotonous and lacked variety. The aim of training in using multiplication smart board learning media is to increase students' interest in counting and provide media that is more fun and interesting for students so that students do not get bored easily when learning to count. Implementation of community service activities uses the Participatory Action Research (PAR) method. Action and participatory methods are implemented in mentoring activities to introduce learning media created by the community service team. The result of this community service activity is that students' abilities have increased after being given training in using learning media in the form of multiplication boards and students are finding it easier to solve problems related to basic arithmetic material, especially multiplication, students are also more likely to solve basic arithmetic story problems in everyday life.